Yiqi Fumai Injection as an Adjuvant Therapy in Treating Chronic Heart Failure: A Meta-Analysis of 33 Randomized Controlled Trials. (19th August 2020) - Nie, Heyun; Li, Shuqing; Liu, Meilu; Zhu, Weifeng; Zhou, Xu; Yan, Dongmei
Abstract : Background . Yiqi Fumai injection (YQFM) is a traditional Chinese medicine widely used for cardiovascular diseases in China. This systematic review aimed to evaluate whether YQFM could be an effective and safe complementary therapy for chronic heart failure (CHF). Methods . Eight electronic literature databases were searched up to March 31, 2020. Randomized controlled trials (RCTs) comparing YQFM + conventional treatment with conventional treatment alone for CHF were included. The primary outcome was response to treatment, which was graded by improvements in heart function based on the New York Heart Association (NYHA) criteria, while the secondary outcomes included the left ventricular ejection fraction (LVEF), cardiac output, left ventricular end-systolic diameter (LVESD), amino-terminal pro-brain natriuretic peptide (NT-proBNP), 6-minute walk test performance (6MWT), quality of life (QoL) as assessed by the Minnesota Living with Heart Failure questionnaire, and adverse reactions. Data from individual RCTs were pooled by a random-effects meta-analysis with effect measures of proportional odds ratios (pORs) and 95% confidence intervals (95% CIs) for the ordinal outcomes and the mean difference (MD) and 95% CI for the continuous outcomes. Results . In total, 33 RCTs involving 3070 patients with an overall moderate-to-high risk of bias were selected. The meta-analysis showed that compared with conventional treatment alone, YQFM plus conventional treatment had a significantly higher likelihood of improving the response to treatment (pOR 1.88, 95% CI 1.47 to 2.42, I 2  = 0%). YQFM also significantly improved the LVEF (MD 5.53%, 95% CI 4.73 to 6.33, I 2  = 82%), cardiac output (MD 0.32 L/min, 95% CI 0.19 to 0.45, I 2  = 47%), and LVESD (MD −3.73 mm, 95% CI −5.51 to −1.95, I 2  = 22%), reduced the NT-proBNP levels (MD −341.83 pg/mL, 95% CI −417.89 to −265.77, I 2  = 88%), and improved the 6MWT (MD 61.86 m, 95% CI 45.05 to 78.67, I 2  = 64%) and QoL (MD −9.82, 95% CI −14.17 to −5.46, I 2  = 81%). No serious adverse events related to YQFM were reported. Conclusion . Although limited by a moderate-to-high risk of bias, the current evidence suggests that YQFM as a complementary treatment significantly improves heart function and related indicators in patients with CHF. The clinical use of YQFM needs careful safety monitoring. Well-designed studies are still required to further evaluate the efficacy and safety of YQFM for CHF.